Fundamental orthopedic management for the physical therapist assistant - Manske, Robert C. (Missouri: Elsevier, 2016)
Master the role and the skills of the physical therapist assistant! Fundamental Orthopedic Management for the Physical Therapist Assistant, 4th Edition helps you apply the principles of orthopedic science to physical therapy interventions. First you will learn how to assess flexibility, strength, endurance, and balance, and then you'll become a more valuable PTA by learning the essentials of tissue healing, gait and manual therapy, biomechanics and kinesiology, and the management of orthopedic patients by region and condition. This edition includes a new full-color design and illustrations. --
Part 1: Basic Concepts Of Orthopedic Management -- 1: Patient supervision and observation during treatment / Candy Bahner -- 2: The role of the physical therapist assistant in physical assessment / Candy Bahner, Jamie Dehan -- 3: Differential diagnosis and emergent conditions / Daryl Menke, Jeromy Jones, Robert C. Manske -- 4: Muscle flexibility and range of motion / Harvey W. Wallmann -- 5: Muscle strength / Marc Campolo -- 6: Endurance / Jason Brumitt -- 7: Balance and coordination / Bryan Riemann -- Part 2: Review Of Tissue Healing -- 8: Composition and function of connective tissue / Erik P Meira -- 9: Ligament healing / Robert C. Manske, John DeWitt -- 10: Bone healing / Robert C. Manske, B. J. Lehecka -- 11: Cartilage healing / Erik P Meira -- 12: Muscle and tendon healing / Jason Brumitt -- 13: Neurovascular healing and thromboembolic disease / Barbara Smith -- Part 3: Basis for movement -- 14: Fundamentals of normal and abnormal gait / Thomas W. Kernozek, John D. Willson -- 15. Concepts of joint and soft tissue mobiliazation / Robert C. Manske, Justin Rohrberg, B. J. Lehecka -- 16. Biomechanics and kinesiology / Michael Hales -- Part 4: Management Of Orthopedic Conditions By Region -- 17: Orthopedic management of the angle, foot, and toes / Walter L Jenkins, Blaise Williams -- 18: Orthopedic management of the knee / John T. Cavanaugh, Jessica hettler, Victoria Moran, Pawel Wawrzyniak -- 19: Orthopedic management of the hip and pelvis / Michael P. Reiman -- 20: Orthopedic management of the lumbar, thoracic, and cervical spine / Cheryl Sparks, Joseph Kelly, Gary A. Shankman -- 21: Orthopedic management of the shoulder / Terry Trundle -- 22: Orthopedic management of the elbow / Leonard C. Macrina -- 23: Orthopedic management of the wrist and hand / Marsha Lawrence -- Part 6: Management Of Orthopedic Conditions By Condition -- 24: Orthopedic management of rheumatic disorders / Steven Elliott -- 25: Orthopedic managemtn of pain and pain syndromes / Adriaan Louw, Terry Cox -- 26: Orthopedic management of orthotics and prosthetics / Leslie K. King -- 27. Musculoskeletal-related dysfunctions of the pelvic floor / Jennifer E. Celso -- Part 3: Topics in orthopedics -- 28. Concepts of orthopedic pharmacology / Ladonna S. Hale -- 29: Musculoskeletal imaging / Terry Malone, Charles Hazel -- Appendices -- A: Commonly used medications in orthopedics / LaDonna S Hale -- B: Reference ranges for commonly used tests / Amy Hassen, Jaime C. Paz -- C: Units of measurement and terminology for the description of exercise and sport performance / Amy Hassen, Jaime C. Paz -- D: Fracture eponyms / Amy Hassen, Jaime C. Paz -- E: Major movements of the body and the muscles acting on the joints causing the movement / Amy Hassen, Jaime C. Paz.
Keywords: Allied health personnel; Orthopedics; Physical therapy assistants; Physical therapy; Orthopedic Procedures; Physical Therapist Assistants; Physical Therapy Modalities; Allied health personnel; Orthopedics; Physical therapy; Physical therapy assistants